2020
DOI: 10.3390/nu12082290
|View full text |Cite
|
Sign up to set email alerts
|

Is Caloric Restriction Associated with Better Healthy Aging Outcomes? A Systematic Review and Meta-Analysis of Randomized Controlled Trials

Abstract: Background: Global dietary patterns have gradually shifted toward a ‘western type’ with progressive increases in rates of metabolic imbalance. Recently, animal and human studies have revealed positive effects of caloric restriction (CR) on many health domains, giving new knowledge for prevention of ill and health promotion; Methods: We conducted a systematic review (SR) of randomized controlled trials (RCTs) investigating the role of CR on health status in adults. A meta-analysis was performed on anthropometri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 86 publications
0
20
1
Order By: Relevance
“…In the present study, exercise intervention was designed as an RS exercise, and no effects of exercise intervention were found on the participants’ CV health. Although a few studies have demonstrated the improvement of LDL-C levels by CR or exercise intervention [ 23 , 30 , 31 ], in the present study, we only observed the improvement of LDL-C levels by the CR and RS combined intervention. The lack of improvement with CR or RS alone may be due to the short duration of the intervention in this study, but to some extent, it suggests that the combined intervention of CR and exercise may have a more significant effect on lipid levels [ 32 ].…”
Section: Discussioncontrasting
confidence: 76%
See 1 more Smart Citation
“…In the present study, exercise intervention was designed as an RS exercise, and no effects of exercise intervention were found on the participants’ CV health. Although a few studies have demonstrated the improvement of LDL-C levels by CR or exercise intervention [ 23 , 30 , 31 ], in the present study, we only observed the improvement of LDL-C levels by the CR and RS combined intervention. The lack of improvement with CR or RS alone may be due to the short duration of the intervention in this study, but to some extent, it suggests that the combined intervention of CR and exercise may have a more significant effect on lipid levels [ 32 ].…”
Section: Discussioncontrasting
confidence: 76%
“…Although CR and exercise intervention were differently designed in various studies, prior results provided evidence that CR and exercise leads to weight loss and improvements in body composition [ 23 ]. In CALERIE phase one trials, Michael et al demonstrated that 6 months of CR with or without exercise resulted in similar weight loss (10%) [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Diet modification, in particular caloric restriction (CR), is a crucial component in the treatment of obesity [ 6 , 7 ]. It has been suggested that both intermittent and continuous CR may provide beneficial effects in promoting weight loss and metabolic improvements in overweight/obese men and women [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Caloric restriction (CR), the significant decrease in calorie intake, is a strategy for improving health and increasing lifespan ( Madeo et al, 2019 ). It has been shown to improve heart function, suppress markers of inflammation and reduce the risk of CVDs and diabetes in humans ( Caristia et al, 2020 ; Kirkham et al, 2020 ). The beneficial effects of CR occur through an extreme wide range of molecular mechanisms, largely overlapping with epigenetic factors like sirtuins ( Gensous et al, 2019 ) and the promotion of autophagy process ( Abdellatif et al, 2018 ).…”
Section: Clinical Application Prospect In Aging and Cvdsmentioning
confidence: 99%